(untitled) (Journal of Hama University, 2026)
Introduction: The psychological impact of Polycystic Ovary Syndrome (PCOS) is directly associated with its physical manifestations and symptoms. Women affected by PCOS often report lower levels of body satisfaction compared to unaffected women, which may lead to body image disturbance. This disturbance is characterized by an excessive and irrational focus on perceived physical flaws, largely due to the importance placed on physical appearance in self-evaluation among women. Aim: To assess body image disturbance among women diagnosed with PCOS in the city of Latakia. Material and Methods: A descriptive study was conducted in the gynecology and obstetrics clinics of the Maternity and Children’s Hospital and Latakia University Hospital. The sample included 40 women diagnosed with PCOS during the study period. Data were collected using a structured questionnaire that included demographic and health-related information, along with the Body Image Scale. Statistical analysis was performed using SPSS software. Results: Findings revealed that 72.5% of participants had a negative body image, while 20% had a neutral perception. Higher body image scores were observed among married women, those of normal weight, without hirsutism, and aged between 25 and under 35 years. Recommendations: The study recommends providing psychological support and educational programs to raise awareness about body image and reduce its negative psychological effects. It also calls for future research to explore associated psychological disorders for a deeper understanding.